La educación infantil de 0 a 3 años - Goldschmied, Elinor, (Colección Pedagogía (Ediciones Morata). Manuales., 2000)
People Under Three proposes a new approach to group day care of very young children, translating child development theory and research into everyday practice. All the ideas in the book have been developed and tested in nurseries and family centres in Britain and overseas, and will appeal to a wide range of people involved in child care. The authors have brought together their immense range of relevant experience to produce a book which will be of direct practical use to policy makers, managers, child care workers, social workers and students, as well as to parents themselves.